Enhanced Photocatalytic Degradation and Mineralization of Furfural Using UVC/TiO2/GAC Composite in Aqueous Solution - Bahram Ghasemi; Bagher Anvaripour; Sahand Jorfi; Neematollah Jaafarzadeh (International Journal of Photoenergy)
Titanium dioxide nanoparticles were immobilized on granular activated carbon (GAC) as a porous and low-density support for photocatalytic degradation of furfural. The TiO2/GAC composite was synthetized using the simple sol-gel method and fully characterized. The effects of the operational parameters of furfural concentration (200–700 mg/L), initial pH (2–12), TiO2/GAC composite dosage (1–3.5 g/L), and irradiation time (20–120 min) were studied. The synthetized TiO2/GAC composite exhibited a total pore volume of 0.13 cm3/g and specific surface area of 35.91 m2/g. Removal efficiency of up to 95% was observed at initial pH of 10, TiO2/GAC dosage of 2.5 g/L, irradiation time of 80 min, and initial furfural concentration of 500 mg/L. The photocatalyst could be reused at least four consecutive times with a mere 2% decrease in furfural removal efficiency. Mineralization efficiency of 94% was obtained within 80 min. Pseudo-first-order kinetics best fit the photocatalytic degradation of furfural under experimental conditions.